Infection capacity of fungi associated with dry rot disease of yam tubers : Fungal infection - Sánchez López, Diana Beatriz (2021)
Dry rot of tubers is one of the most devastating diseases in yam production (Dioscorea rotundata Poir.) in the Caribbean region of Colombia. The disease attacks tubers causing production losses during the crop. In previous experiments, 11 fungal morphotypes were isolated and associated with this disease in yam crops in the Caribbean region of Colombia. The present investigation was carried out under greenhouse conditions to determine the infection capacity of these 11 possible causative agents, in 150-day-old plants of two yam genetic materials (0307-49SB y 0307-50CB). The results indicated that morphotypes DH2 (Lasiodiplodia theobromae), DH11 (Curvularia aeria), DH20 (Aspergillus niger), and DH17 (Fusarium equiseti), showed the highest infection capacity to yam tubers, regardless of the genetic material, therefore, they were considered as the main causal agents of the disease in the Caribbean region of Colombia. The remaining seven (7) morphotypes, despite having been inoculated in the roots of the plants, showed minor effects on tubers and affected other organs of the plant, especially stems and aerial part of yam plant. This study allows concentrating the research on these four morphotypes to develop crop management strategies that might allow reducing the incidence of this disease in the Caribbean region of Colombia.